2018
DOI: 10.1007/s00464-018-6366-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of perforated peptic ulcers: laparoscopic versus open approach

Abstract: Fewer than 10% of patients with perforated peptic ulcers underwent LS, which was associated with reduced length of stay, lower rate of superficial surgical site infections, wound dehiscence, and mortality. Given our results, a greater emphasis should be provided to a minimally invasive approach for the surgical repair of perforated peptic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 63 publications
6
28
0
8
Order By: Relevance
“…Included studies were published between 1996 and 2019. Five were RCTs [14][15][16][17][18] , three were prospective cohort studies [19][20][21] , and the other 15 studies used retrospective cohort or case-control designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ( Table 1). All compared outcomes of laparoscopic versus open peptic ulcer repair.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published between 1996 and 2019. Five were RCTs [14][15][16][17][18] , three were prospective cohort studies [19][20][21] , and the other 15 studies used retrospective cohort or case-control designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ( Table 1). All compared outcomes of laparoscopic versus open peptic ulcer repair.…”
Section: Resultsmentioning
confidence: 99%
“…Its overall mortality rate is between 1.3% and 20%, whereas mortality due to perforation of the stomach ulcer is more than that of duodenal ulcer (40% vs 10%). 4 The omental patch is a common surgical answer to ulcerative perforation; however, 4 in some cases, omentum may not be available due to previous omental surgeries, inflammation, and adhesion caused by necrotic pulmonary peritonitis, or through penetration of the perforation site. 5 Furthermore, because of the postoperative ileus, stomach, and intestinal stretch, causing stretch at the omentum, postoperative suture leakage and opening can occur.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 4 SRs (2 older SRs were excluded 53,54 ), 2 RCTs, and 7 observational studies on laparoscopic repair of perforated peptic ulcers. [55][56][57][58][59][60][61][62][63][64][65] An SR (3 RCTs) found trends toward lower septic complications, SSI, ileus, and mortality with laparoscopy, and significantly shorter LOS in 1 RCT. 55,[66][67][68] An older SR (56 articles) found that laparoscopy is associated with decreased LOS, postoperative pain, and morbidity and mortality, but increased operating time and recurrent leak.…”
Section: Evidencementioning
confidence: 99%
“…57,58 Seven observational studies generally found shorter LOS and decreased morbidity and mortality. [59][60][61][62][63][64][65] We identified 2 SRs, 2 MAs, and 13 observational studies (5 studies were in the SRs and were therefore excluded [69][70][71] evaluating laparoscopic vs open emergent colon resections. [72][73][74][75][76][77][78][79][80][81][82][83] One MA (4 observational studies) on urgent or emergent sigmoidectomy for diverticulitis found that laparoscopy decreased complications (RR 0.62; 95% CI, 0.49 to 0.80; p ¼ 0.0002).…”
Section: Evidencementioning
confidence: 99%